Establishment and early growth of stump and stripling transplants of Terminalia irovensis when interplanted with corn, cowpeas, and beans [Zea mays, Vigna unguiculata, Phaseolus vulgaris]. - Magne Ojeda, Jaime (1979)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1979